Mega project : ACP Industries Berhad / Aishah Jaffar … [et al.] - Jaffar, Aishah (Faculty of Business and Management, 2001)
Industrial products industry is not a newly industry in this century. Perhaps it is significant areas whereby public demand is very accountable due to economic condition, environment threats and explored new technology. Quality services is always needed and upheaval rapidly in order to provide the customer with quality product and services. Therefore ACP Industries as a strong reputation or implementing market-oriented strategists and efficient management of the business, must continuously research consumer needs, preference and practices to keep pace with trends in the future. In order to increase the profit and revenues bear in mind that mission, objective and strategies of company are very important.